Pengaruh Lingkungan Kerja, Kompensasi dan Stress Kerja terhadap Loyalitas Karyawan - Novia Tri Ratnasari; Jajuk Herawati; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to examine the effect of work environment, compensation and work stress on employee loyalt. This type of research used is quantitative research. This study uses the census method, which takes all the population as research respondents. The number of respondents is 55 people and the results of the analysis using SPSS Version 23. Based on the results of the analysis on the data, it can be concluded that the work environment has a positive and insignificant effect on the employee loyalty variable, the work environment plays an important role in the quality of employee loyalty (1) Compensation has a positive and significant effect on employee loyalty, the importance of compensation is as follows: one indicator of job satisfaction (2) Work stress has no significant effect on employee loyalty, work stress is something that often happens in a workplace and stress is a process of one's thoughts, emotions and physical condition. (3) Work environment, compensation and work stress simultaneously affect employee loyalty (4). Keywords: Work environment, compensation, work streses and employee loyalty